The effects of hydrogen peroxide on mortality, escape response, and oxygen consumption of Calanus spp. - Rosa H. Escobar-Lux; David M. Fields; Howard I. Browman; Steven D. Shema; Reidun M. Bjelland; Ann-Lisbeth Agnalt; Anne Berit Skiftesvik; Ole B. Samuelsen; Caroline M.F. Durif (Canadian Science Publishing, 2019)
Hydrogen peroxide (H2O2), a pesticide used in salmonid aquaculture, is released directly into the environment where nontarget organisms are at risk of exposure. We determined threshold concentrations for mortality of Calanus spp., the dominant zooplankton species in the North Atlantic, and assessed sublethal effects, focusing on the escape response and oxygen consumption rates (OCRs) as behavioral and physiological assays. One-hour exposure to 170 mg·L−1 (i.e., 10% of the recommended H2O2 treatment) was lethal to copepodite stage V (92% mortality) and adult females (100% mortality). The acute median lethal concentration (1h-LC50) was 214.1 (150.67-277.4) and 48.6 (44.9-52.2) mg·L−1 for copepodite V and adults, respectively. The 25-h LC50 was 77.1 (57.9-96.2) and 30.63 (25.4-35.8) mg·L−1 for copepodite V and adults, respectively. At concentrations of 0.5% and 1% of the recommended treatment level, Calanus spp. showed a decrease in escape performance and lower OCRs with increased concentration. At H2O2 concentrations of 5% of the recommended treatment levels (85 mg·L−1), exposed copepods showed no escape reaction response. These results suggest that sublethal concentrations of H2O2 will increase the risk of predation for Calanus spp. Furthermore, this study provides supporting evidence that theoretical "safe" values, traditionally used for predicting toxicity thresholds, underestimate the impact of H2O2 on the physiological condition of nontarget crustaceans.